Resistance of industrial mango peel waste to pectin degradation prior to by-product drying - Sirisakulwat S. (2014)
Susceptibility of industrial mango peel waste to pectin degradation during storage at ambient conditions (25 °C, 63% relative humidity) for up to 5 h before by-product stabilisation by drying was explored. Depending on the interim storage period in the wet state, pectins were recovered from the dried peels by hot-acid extraction. Most important, pectin degradation during the temporary storage of the wet peels was insignificant, as revealed by yields, composition, average molecular properties, and techno-functional quality. Hardly acetylated (DAc 2.5-4.5%), rapid-set high-methoxyl pectins were obtained at starch-corrected net yields of 14.1-15.6 g hg-1. Irrelevant de-esterification during peel storage in the wet state was confirmed by overall uniform setting temperatures. Arabinogalactans, uniformly indicated by high molar galactose/rhamnose ratios of 13.8-16.9 mol/mol and an arabinose percentage of 9.5-14.4 mol hmol-1 of galactose residues, affected the galacturonide contents, intrinsic viscosities, and gel strengths throughout. The wet peels, derived from widespread manual peeling in mango canning, tolerated intermediate storage for 5 h, thus facilitating by-product stabilisation on smaller scales. © 2010 The Authors. Journal compilation © 2010 Institute of Food Science and Technology.